2021
DOI: 10.3889/oamjms.2021.6657
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nutrition Education Using Pocketbook Media on Iron and Protein Intake

Abstract: The provision of nutrition education for teenage girls is an alternative to increase protein and iron intake to prevent anemia. This study aims to determine nutrition education's effect using pocketbook media on protein and iron intake in teenage girls. The research design used was quasi-experimental with a control group pre and post-test design. Sampling was done by the purposive sampling method—statistical analysis using Paired Samples T-test, Wilcoxon, Independent Samples T-test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Material and terms about the nutrition of adolescents and brides use simple words, besides that pocketbooks also contain images with attractive colors and motivational words. This study was in line with the research of Syarief et al which showed that nutrition education using pocketbook media on protein and iron intake in the treatment group [24]. The results of the study also showed a tendency for increasing knowledge, attitudes, and practices in students who received an information and education communication model with the provision of pocketbooks of` anemia.…”
Section: Effect Of Preconception Nutrition Education With Pocket Bookssupporting
confidence: 90%
See 3 more Smart Citations
“…Material and terms about the nutrition of adolescents and brides use simple words, besides that pocketbooks also contain images with attractive colors and motivational words. This study was in line with the research of Syarief et al which showed that nutrition education using pocketbook media on protein and iron intake in the treatment group [24]. The results of the study also showed a tendency for increasing knowledge, attitudes, and practices in students who received an information and education communication model with the provision of pocketbooks of` anemia.…”
Section: Effect Of Preconception Nutrition Education With Pocket Bookssupporting
confidence: 90%
“…The results of this study reinforce the findings of several studies such as Priani et al in this research which preconception education using pocketbooks media increases understanding regarding physical health, nutrition, and lifestyle preconceptions [22]- [24]. Wahyuningsih et al in their research also showed that counseling with pocketbooks on the health and nutrition of the elderly had a significant effect on konowlwdge [22]- [24]. Likewise, Syarief et al proved the same result, namely that nutrition education using pocketbooks increased protein and iron intake in adolescents [22]- [24].…”
Section: Effect Of Preconception Nutrition Education With Pocket Bookssupporting
confidence: 90%
See 2 more Smart Citations
“…Specific behavioral and behavioral factors are associated with the use of markers [12]. In addition, a research result shows a difference in the effect of pocketbook media on consumption behavior so that there is an increase in protein intake [13].…”
Section: Discussionmentioning
confidence: 99%